Rad5 and Its Human Homologs, HLTF and SHPRH, Are Novel Interactors of Mismatch Repair - Miller, Anna K.; Mao, Guogen; Knicely, Breanna G.; Daniels, Hannah G.; Rahal, Christine; Putnam, Christopher D.; Kolodner, Richard D.; Goellner, Eva M. (Frontiers in Cell and Developmental Biology, 2022)
DNA mismatch repair (MMR) repairs replication errors, and MMR defects play a role in both inherited cancer predisposition syndromes and in sporadic cancers. MMR also recognizes mispairs caused by environmental and chemotherapeutic agents; however, in these cases mispair recognition leads to apoptosis and not repair. Although mutation avoidance by MMR is fairly well understood, MMR-associated proteins are still being identified. We performed a bioinformatic analysis that implicated Saccharomyces cerevisiae Rad5 as a candidate for interacting with the MMR proteins Msh2 and Mlh1. Rad5 is a DNA helicase and E3 ubiquitin ligase in involved in post-replicative repair and damage tolerance. We confirmed both interactions and found that the Mlh1 interaction is mediated by a conserved Mlh1-interacting motif (MIP box). Despite this, we did not find a clear role for Rad5 in the canonical MMR mutation avoidance pathway. The interaction of Rad5 with Msh2 and Mlh1 is conserved in humans, although each of the Rad5 human homologs, HTLF and SHPRPH, shared only one of the interactions: HTLF interacts with MSH2, and SHPRH interacts with MLH1. Moreover, depletion of SHPRH, but not HLTF, results in increased resistance to alkylating agents, similar to the loss of MMR, indicating gene duplication led to specialization of the MMR-protein associated roles of the human Rad5 homologs. These results provide insights into how MMR accessory factors involved in the MMR-dependent apoptotic response interact with the core MMR machinery and have important health implications into how human cells respond to environmental toxins, tumor development, and treatment choices of tumors with defects in Rad5 homologs.